Life satisfaction favors reproduction. The universal positive effect of life satisfaction on childbearing in contemporary low fertility countries - Mencarini, Letizia; Vignoli, Daniele; Zeydanli, Tugba; Kim, Jungho (PLoS ONE, 2018)
Do people with higher life satisfaction have more children? Having children requires considerable energy and investment on the part of parents. However, even in countries where contraceptives are easily available and widely used, where having children is optional and most of time the result of an intended action, parenthood has not gone “out of fashion”. This paper tests the hypothesis that higher life satisfaction fosters reproductive behavior. We argue that people satisfied with their overall life feel better prepared to start the monumental task of childrearing. If, it is suggested, life satisfaction facilitates fertility, then this positive link should be observable in contemporary low fertility societies. The hypothesis is tested by taking overall life satisfaction as a determinant of fertility behavior using long longitudinal data available for developed countries: namely for Australia, Germany, Russia, South Korea, Switzerland, the United Kingdom, and the United States. We find that higher levels of subjective well-being are, indeed, associated with a higher probability of having children in all the countries considered. We, therefore, conclude that life satisfaction favors reproduction, at least in low fertility societies.
Keywords: Birth Rate; Female; Humans; Male; Personal Satisfaction; Reproduction; Value of Life